Thermal barrier coating and preparation method of texture thereof

By adopting a multi-layer structure of NiCoCrAlY bonding layer, YSZ layer and RYSZ layer in the thermal barrier coating, combined with the interface texture technology, the thermal mismatch stress problem caused by the difference in expansion coefficient of the thermal barrier coating is solved, which significantly improves the High temperature service life and thermal insulation performance.

CN119194331APending Publication Date: 2024-12-27EAST CHINA UNIV OF SCI & TECH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411295961.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-14
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

During the high-temperature service, the thermal mismatch stress and growth stress caused by the difference in the expansion coefficient between the bonding layer and the ceramic layer will cause the coating to peel off, reducing the service life of the high-temperature.

Method used

Using a multi-layer structure of NiCoCrAlY bonding layer, YSZ layer and RYSZ layer, the RYSZ layer contains Gd2O3 and Yb2O3, which improves bonding strength and strain tolerance through the interface texture, inhibits oxygen permeation and TGO growth.

Benefits of technology

It significantly improves the high-temperature service life and thermal insulation performance of thermal barrier coating, reduces thermal mismatch stress and growth stress, and extends the service life of the coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119194331A_ABST
    Figure CN119194331A_ABST
Patent Text Reader

Abstract

The invention provides a thermal barrier coating and a preparation method thereof, and belongs to the technical field of coatings. The thermal barrier coating provided by the invention comprises a NiCoCrAlY bonding layer, a YSZ layer and an RYSZ layer which are sequentially stacked, the RYSZ layer is prepared from the following components: Gd2O3, Yb2O3 and ZrO2; the mass of the Gd2O3 and the mass of the Yb2O3 are independently 6 to 25 percent of the mass of the ZrO2. Compared with YSZ and RYSZ, due to existence of Gd2O3 and Yb2O3 in the RYSZ, permeation of oxygen can be inhibited, oxidation of a NiCoCrAlY bonding layer and growth of TGO can be inhibited, the residual stress of a thermal barrier coating system is reduced, and the high-temperature service life is prolonged; gd2O3 and Yb2O3 in the RYSZ can also improve the thermal stability of the coating, and ZrO2 in the RYSZ is prevented from phase change, so that the high-temperature service life of the thermal barrier coating is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of coatings, and in particular to a thermal barrier coating and a preparation method thereof. Background Art

[0002] Thermal barrier coating is a kind of functional coating which uses a material with relatively low thermal conductivity and is coated on the surface of a high-temperature alloy substrate using appropriate technology to provide heat insulation.

[0003] The thermal barrier coating used in large-scale industrial applications is a plasma sprayed double-layer structure system, including an MCrAlY (M = Ni, Co or Ni) bonding layer and a ceramic thermal insulation layer (such as ZrO2-8wt.% Y2O3 yttria stabilized zirconia material, YSZ). During high-temperature service, a thermally grown oxide TGO layer will be generated at the bonding layer-ceramic layer interface. However, the expansion coefficient of the bonding layer is 10 -16 ×10 -6 / K, the expansion coefficient of the TGO layer is 5 -9 ×10 -6 / K, the expansion coefficient of the YSZ ceramic layer is 10 -11 ×10 -6 / K), the expansion coefficients of the three are very different, and thermal mismatch stress is generated near the TGO layer. As the service time increases, the TGO layer grows and thickens, and a large growth stress will accumulate. Under the combined effect of thermal mismatch stress and growth stress, normal residual tensile stress is continuously accumulated at the protrusions of the bonding layer and the pits of the ceramic layer. In addition, high-temperature sintering stiffening and phase change stresses will also be generated inside the ceramic layer. When the elastic strain energy accumulated at the ceramic layer or the interface between the bonding layer and the ceramic layer exceeds the fracture toughness of the coating, microcracks initiate and expand, and then peel off from the metal matrix; and the phase change of YSZ in a high-temperature environment will also promote the peeling of the ceramic layer, which makes the high-temperature service life of the thermal barrier coating lower. Summary of the invention

[0004] The object of the present invention is to provide a method for preparing a thermal barrier coating and its interface texture. The thermal barrier coating of the present invention has a long high-temperature service life and improved service performance.

[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0006] The present invention provides a thermal barrier coating, comprising a NiCoCrAlY bonding layer, a YSZ layer and a RYSZ layer stacked in sequence;

[0007] The composition of the RYSZ layer includes Gd2O3, Yb2O3 and ZrO2;

[0008] The mass of Gd2O3 and the mass of Yb2O3 are independently 6 to 25% of the mass of ZrO2.

[0009] Preferably, the thickness of the RYSZ layer is 50-150 μm.

[0010] Preferably, the thickness of the YSZ layer is 100-350 μm; the mass content of Y2O3 in the YSZ layer is 7-8%.

[0011] Preferably, the thickness of the NiCoCrAlY bonding layer is 40-800 μm.

[0012] Preferably, the NiCoCrAlY bonding layer comprises a NiCoCrAlY bonding layer plane layer and an interface texture on the surface of the NiCoCrAlY bonding layer plane layer; the interface texture is in contact with the YSZ layer;

[0013] The shape of the interface texture includes one or more of a cylindrical shape, a stripe shape and a square shape.

[0014] Preferably, the YSZ layer includes a YSZ plane layer and an interface texture on the surface of the YSZ plane layer; the interface texture is in contact with the RYSZ layer;

[0015] The shape of the interface texture includes one or more of a cylindrical shape, a stripe shape and a square shape.

[0016] The present invention also provides a method for preparing the thermal barrier coating according to the above technical solution, comprising the following steps:

[0017] Performing a first spraying of NiCoCrAlY powder on the metal surface to form a NiCoCrAlY bonding layer;

[0018] Performing a second spraying of YSZ powder on the surface of the NiCoCrAlY bonding layer to form a YSZ layer;

[0019] The RYSZ powder is sprayed on the surface of the YSZ layer for the third time to form a RYSZ layer, thereby obtaining the thermal barrier coating.

[0020] Preferably, the NiCoCrAlY powder comprises, by mass fraction, 18-28% Co, 13-21% Cr, 10-15% Al, 0.1-0.8% Y, ≤5% impurities and the balance Ni.

[0021] Preferably, when the NiCoCrAlY bonding layer includes a NiCoCrAlY bonding layer plane layer and an interface texture on the surface of the NiCoCrAlY bonding layer plane layer, the first spraying includes: first spraying to form the NiCoCrAlY bonding layer plane layer, and then placing a mask corresponding to the shape of the interface texture and then performing a first "spraying" to form the interface texture.

[0022] Preferably, when the YSZ layer includes a YSZ plane layer and an interface texture on the surface of the YSZ plane layer, the second spraying includes: after the second 'spraying forms the YSZ plane layer, a mask corresponding to the shape of the interface texture is placed and then the second 'spraying is performed to form the interface texture.

[0023] The present invention provides a thermal barrier coating, comprising a NiCoCrAlY bonding layer, a YSZ layer and a RYSZ layer stacked in sequence; the composition of the RYSZ layer includes Gd2O3, Yb2O3 and ZrO2; the mass of the Gd2O3 and the mass of the Yb2O3 are independently 6-25% of the mass of ZrO2. Compared with YSZ, the presence of Gd2O3 and Yb2O3 in RYSZ can inhibit the penetration of oxygen, inhibit the oxidation of the NiCoCrAlY bonding layer and the growth of TGO, reduce the residual stress of the thermal barrier coating system, and improve the high-temperature service life; Gd2O3 and Yb2O3 in RYSZ can also improve the thermal stability of the coating, avoid the phase change of ZrO2 in RYSZ, thereby improving the high-temperature service life of the thermal barrier coating. Furthermore, the interface texture located on the surface of the RYSZ layer improves the bonding strength and life of the coating, so that the coating has higher strain tolerance and thermal insulation performance.

[0024] Furthermore, during high-temperature service, the interface texture of the thermal barrier coating of the present invention improves the bonding strength with RYSZ, thermal shock resistance and service life. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 The thermal barrier coating in Example 1 when the interface texture is a square interface texture;

[0026] Figure 2 The thermal barrier coating in Example 1 when the interface texture is a cylindrical interface texture;

[0027] Figure 3 The thermal barrier coating in Example 1 when the interface texture is a stripe interface texture;

[0028] Figure 4 The bonding layer interface texture layer of Example 2;

[0029] Figure 5 This is a SEM image of the YSZ layer in the thermal barrier coating of comparative example 1 after the thermal barrier coating was subjected to 50 thermal cycle tests at 1100° C.;

[0030] Figure 6 This is a SEM image of the thermally grown oxide layer in the thermal barrier coating of Comparative Example 1 after the thermal barrier coating was subjected to 50 thermal cycle tests at 1100° C.;

[0031] Figure 7This is a SEM image of the YSZ layer in the thermal barrier coating of Example 1 after the thermal barrier coating was subjected to 50 thermal cycle tests at 1100° C.;

[0032] Figure 8 This is a SEM image of the thermally grown oxide layer in the thermal barrier coating of Example 1 after the thermal barrier coating was subjected to 50 thermal cycle tests at 1100° C.;

[0033] Fig. 9 The bonding layer interface texture layer of Comparative Example 3;

[0034] Fig.10 The actual pictures of the thermal barrier coatings of Example 2, Comparative Example 2 and Comparative Example 3 after 50 thermal cycle tests;

[0035] Fig.11 This is the interface morphology of the thermal barrier coating with interface texture in comparative example 2;

[0036] Fig.12 This is a real picture of the spraying tool used for preparing the interface texture in the example, wherein 1 is a fixture for fixing the thermal barrier coating substrate, and 2 is a baffle at the front groove of the fixture. DETAILED DESCRIPTION

[0037] The present invention provides a thermal barrier coating, comprising a NiCoCrAlY bonding layer, a YSZ layer and a RYSZ layer stacked in sequence;

[0038] The composition of the RYSZ layer includes Gd2O3, Yb2O3 and ZrO2;

[0039] The mass of Gd2O3 and the mass of Yb2O3 are independently 6 to 25% of the mass of ZrO2.

[0040] In the present invention, the thickness of the NiCoCrAlY bonding layer is preferably 40 to 800 μm, more preferably 200 to 600 μm, and further preferably 300 to 500 μm.

[0041] In the present invention, the NiCoCrAlY bonding layer is preferably a planar layer, and the NiCoCrAlY bonding layer more preferably includes a NiCoCrAlY bonding layer planar layer and an interface texture on the surface of the NiCoCrAlY bonding layer planar layer; the interface texture is in contact with the YSZ layer; the shape of the interface texture includes one or more of cylindrical, strip and square. The spacing of the interface texture is preferably 0.1 to 200 mm, more preferably 50 to 150 mm, and more preferably 80 to 120 mm; the height is preferably 10 to 2000 μm, more preferably 200 to 1500 μm, and more preferably 500 to 1000 μm; the length of the square interface texture is preferably 0.01 to 1000 mm, more preferably 200 to 800 mm, and more preferably 400 to 600 mm; the width is preferably 20 to 2000 μm, more preferably 200 to 1500 μm, and more preferably 500 to 1000 μm. The diameter of the cylindrical interface texture is preferably 1.5 to 3 mm; the width of the strip interface texture is preferably 3 mm, and the length is preferably the length of the surface of the plane layer of the NiCoCrAlY bonding layer.

[0042] In the present invention, the thickness of the YSZ layer is preferably 100 to 350 μm, more preferably 110 to 140 μm, and further preferably 120 to 130 μm; the mass content of Y2O3 in the YSZ layer is preferably 7 to 8%.

[0043] In the present invention, the YSZ layer is preferably a planar layer, and the YSZ layer more preferably includes a YSZ planar layer and an interface texture on the surface of the YSZ planar layer; the interface texture is preferably in contact with the RYSZ layer; the thickness of the YSZ planar layer is preferably 100-150 μm; the shape of the interface texture preferably includes one or more of cylindrical, strip and square; the spacing of the interface texture is preferably 0.1-200 mm, more preferably 50-150 mm, and further preferably 80-120 mm; the height is preferably 10-2000 μm, more preferably 200-1500 μm, and further preferably 500-1000 μm; the length of the square interface texture is preferably 0.01-1000 mm, more preferably 200-800 mm, and further preferably 400-600 mm; the width is preferably 20-2000 μm, more preferably 200-1500 μm, and further preferably 500-1000 μm. The diameter of the cylindrical interface texture is preferably 1.5 to 3 mm; the width of the strip interface texture is preferably 3 mm, and the length is preferably the length of the surface of the YSZ layer where it is located.

[0044] In the present invention, the thickness of the RYSZ layer is preferably 50 to 150 μm, more preferably 60 to 120 μm, and further preferably 80 to 100 μm; the components of the RYSZ layer include Gd2O3, Yb2O3 and ZrO2; the mass of Gd2O3 and the mass of Yb2O3 are independently 6 to 25% of the mass of ZrO2, preferably independently 10 to 20%, and more preferably 15 to 18%.

[0045] In the present invention, RYSZ has a higher density than YSZ due to the presence of doped oxides, thereby inhibiting the penetration of oxygen. At the same time, the oxidation of the NiCoCrAlY bonding layer and the growth of TGO are inhibited, the residual stress of the thermal barrier coating system is reduced, and the high-temperature service life is improved. The doped oxide in RYSZ can also prevent the phase change of ZrO2 in RYSZ, thereby improving the high-temperature service life of the thermal barrier coating.

[0046] The present invention also provides a method for preparing the thermal barrier coating described in the above scheme, comprising the following steps:

[0047] Performing a first spraying of NiCoCrAlY powder on the metal surface to form a NiCoCrAlY bonding layer;

[0048] Performing a second spraying of YSZ powder on the surface of the NiCoCrAlY bonding layer to form a YSZ layer;

[0049] The RYSZ powder is sprayed on the surface of the YSZ layer for the third time to form a RYSZ layer, thereby obtaining the thermal barrier coating.

[0050] The present invention performs a first spraying of NiCoCrAlY powder on the metal surface to form a NiCoCrAlY bonding layer. In the present invention, the metal preferably includes a nickel-based alloy, and the nickel-based alloy preferably includes GH3230.

[0051] In the present invention, the first spraying is preferably atmospheric plasma spraying; the current of the first spraying is preferably 290-550A, more preferably 300-500A, and further preferably 400-450A; the voltage is preferably 40-56V, more preferably 42-50V, and further preferably 45-48V; the power is preferably 2.75-40kW, more preferably 10-30kW, and further preferably 15-20kW; the argon flow rate of the first spraying is preferably 1-40NLPM / min, more preferably 10-30NLPM / min, and further preferably 15-20NLPM / min; the hydrogen The air flow rate is preferably 6-20NLPM / min, more preferably 12-18NLPM / min, and further preferably 15-16NLPM / min; the powder feed rate is preferably 3-45g / min, more preferably 5-40g / min, and further preferably 20-30g / min; the spraying distance is preferably 10-100mm, more preferably 20-80mm, and further preferably 40-60mm; the gun speed is preferably 350-800mm / s, more preferably 400-600mm / s, and further preferably 450-500mm / s; the gun interval is preferably 1-3mm.

[0052] When the NiCoCrAlY bonding layer includes a NiCoCrAlY bonding layer planar layer and an interface texture on the surface of the NiCoCrAlY bonding layer planar layer, the first spraying preferably includes: a first 'spraying to form the NiCoCrAlY bonding layer planar layer, and then placing a mask corresponding to the shape of the interface texture and then performing a first 'spraying to form the interface texture; the process parameters of the first 'spraying and the first 'spraying may be the same or different, but are both within the range of the process parameters of the first spraying.

[0053] In the present invention, the NiCoCrAlY powder preferably comprises, by mass fraction, Co 18-28%, Cr 13-21%, Al 10-15%, Y 0.1-0.8%, impurities ≤5% and the balance Ni; the particle size of the NiCoCrAlY powder is preferably 40-140 μm.

[0054] After forming the NiCoCrAlY bonding layer, the present invention performs a second spraying of YSZ powder on the surface of the NiCoCrAlY bonding layer to form a YSZ layer. In the present invention, the second spraying is preferably atmospheric plasma spraying; the current, voltage, power, argon flow rate, hydrogen flow rate, powder feeding rate, spraying distance, gun travel speed and gun travel interval of the second spraying of the present invention are preferably consistent with the range of the first spraying conditions, which will not be repeated here. In the present invention, the particle size of the YSZ powder is preferably 40 to 140 μm.

[0055] When the YSZ layer includes a YSZ planar layer and an interface texture on the surface of the YSZ planar layer, the second spraying includes: after the second 'spraying forms the YSZ planar layer, a mask corresponding to the shape of the interface texture is placed and then a second 'spraying is performed to form the interface texture; the process parameters of the second 'spraying and the second 'spraying may be the same or different, but are both within the process parameter range of the second spraying.

[0056] After the YSZ layer is formed, the present invention performs a third spraying of RYSZ powder on the surface of the YSZ layer to form a RYSZ layer, thereby obtaining the thermal barrier coating.

[0057] In the present invention, the method for preparing the RYSZ powder preferably comprises the following steps:

[0058] Gd2O3, Yb2O3 and Zr2O3 are mixed and calcined, and then the calcined product is ball milled.

[0059] In the present invention, the calcination temperature is preferably 1000° C. and the calcination time is preferably 24 hours.

[0060] In the present invention, the particle size of the RYSZ powder is preferably 40 to 140 μm.

[0061] In the present invention, the third spraying is preferably atmospheric plasma spraying; the current, voltage, power, argon flow rate, hydrogen flow rate, powder feeding rate, spraying distance, gun speed and gun interval of the third spraying of the present invention are preferably consistent with the range of the first spraying conditions, and will not be repeated here.

[0062] The thermal barrier coating and the preparation method thereof provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0063] The preparation method of RYSZ powder in the embodiment is:

[0064] 5 parts of Gd2O3, 5 parts of Yb2O3 and 20 parts of Zr2O3 were mixed and calcined at 1000°C for 24h, and then the calcined product was ball milled.

[0065] Fig.12 This is a real picture of the spraying tool used for preparing the interface texture in the example, wherein 1 is a fixture for fixing the thermal barrier coating substrate, and 2 is a baffle at the front groove of the fixture.

[0066] Example 1

[0067] GH3230 nickel-based high-temperature alloy was selected as the substrate, and circular sheet specimens were prepared through wire cutting and polishing processing technology.

[0068] The surface of the disc was sandblasted with 36 mesh white corundum to enhance its surface roughness and adhesion, and was fully ultrasonically cleaned with alcohol and dried to obtain a GH3230 matrix.

[0069] NiCoCrAlY (powder particle size of corresponding components is 40-60 μm; mass contents of Ni, Co, Cr, Al, Y and impurities are 38.2%, 26%, 20%, 14%, 0.8% and 1% respectively) is sprayed on GH3230 substrate by atmospheric plasma spraying equipment to obtain a NiCoCrAlY bonding layer with a thickness of 100 μm; wherein the spraying current is 340A, the voltage is 43.2V, the power is 15kW, the argon flow rate is 1.9NLPM / min, the hydrogen flow rate is 17.6NLPM / min, the powder feeding rate is 32g / min, the spraying distance is 15mm, the gun travel speed is 600mm / s, and the gun travel interval is 1mm;

[0070] YSZ powder (particle size of 40-140 μm, Y2O3 content of 7% by mass and balance of ZrO2) was sprayed on the NiCoCrAlY bonding layer by atmospheric plasma spraying equipment to obtain a YSZ plane layer with a thickness of 100 μm. The spraying current was 319 A, the voltage was 43.2 V, the power was 13.7 kW, the argon flow rate was 1.9 NLPM / min, the hydrogen flow rate was 15.7 NLPM / min, the powder feeding rate was 32 g / min, the spraying distance was 15 mm, the gun travel speed was 600 mm / s, and the gun travel interval was 1 mm.

[0071] After setting the baffle, continue to spray YSZ powder (particle size of 40-140μm, Y2O3 mass content of 7% in YSZ powder, balance ZrO2) to generate YSZ interface texture layer. The power of the plasma spray gun is 37.6kW, the current is 550A, the voltage is 50V, the argon flow rate is 35.7NLPM / min, the hydrogen flow rate is 11NLPM / min, the powder feeding rate is 45g / min, the spraying speed is 800mm / s, the spraying distance between the nozzle and the GH3230 substrate is 10cm, and the gun travel interval is 1mm.

[0072] RYSZ powder (particle size of 40-140 μm) was sprayed on the YSZ layer by atmospheric plasma spraying equipment to obtain a RYSZ layer with a thickness of 50 μm, thereby obtaining a thermal barrier coating. The spraying current was 300A, the voltage was 40V, the power was 12kW, the argon flow rate was 2NLPM / min, the hydrogen flow rate was 16NLPM / min, the powder feeding rate was 30g / min, the spraying distance was 15mm, the gun speed was 600mm / s, and the gun interval was 1mm.

[0073] When the interface texture is a square interface texture (side length is 1.5 mm, the spacing between adjacent square interface textures is 1.5 mm, and the height is 160 μm), the thermal barrier coating prepared is as follows: Figure 1 As shown;

[0074] When the interface texture is a cylindrical interface texture (with a diameter of 1.5 mm, a spacing of 1 mm between adjacent cylindrical interface textures, and a height of 200 μm), the thermal barrier coating prepared is as follows: Figure 2 As shown;

[0075] When the interface texture is a stripe interface texture (width is 3 mm, the spacing between adjacent stripe interface textures is 1.5 mm, and the height is 160 μm), the thermal barrier coating prepared is as follows: Figure 3 shown.

[0076] Example 2

[0077] GH3230 nickel-based high-temperature alloy was selected as the substrate, and circular sheet specimens were prepared through wire cutting and polishing processing technology.

[0078] The surface of the disc was sandblasted with 36 mesh white corundum to enhance its surface roughness and adhesion, and was fully ultrasonically cleaned with alcohol and dried to obtain a GH3230 matrix.

[0079] NiCoCrAlY (powder particle size of corresponding components is 40-140 μm; mass contents of Ni, Co, Cr, Al, Y and impurities are 38.2%, 26%, 20%, 14%, 0.8% and 1% respectively) was sprayed on GH3230 substrate by atmospheric plasma spraying equipment to obtain a NiCoCrAlY bonding layer plane layer with a thickness of 100 μm; wherein the spraying current is 350 A, the voltage is 40 V, the power is 14 kW, the argon flow rate is 2 NLPM / min, the hydrogen flow rate is 18 NLPM / min, the powder feeding rate is 30 g / min, the spraying distance is 15 mm, the gun travel speed is 600 mm / s, and the gun travel interval is 1 mm;

[0080] After setting the baffle, continue to spray NiCoCrAlY (powder particle size of the corresponding component is 40-140μm) to obtain a cylindrical interface texture bonding layer interface texture layer (diameter is 2.5mm, the spacing between adjacent cylindrical interface textures is 1mm, and the height is 200μm). The power of the plasma spray gun is 37.6kW, the current is 550A, the voltage is 50V, the argon flow rate is 35.7NLPM / min, the hydrogen flow rate is 11NLPM / min, the powder feeding rate is 45g / min, the spraying speed is 800mm / s, the spraying distance between the nozzle and the GH3230 substrate is 10cm, and the gun travel interval is 1mm.

[0081] YSZ powder (particle size of 40-140 μm, Y2O3 content of 7% by mass and balance of ZrO2) was sprayed on the NiCoCrAlY bonding layer by atmospheric plasma spraying equipment to obtain a YSZ layer with a thickness of 100 μm. The spraying current was 310 A, the voltage was 40 V, the power was 12.4 kW, the argon flow rate was 2 NLPM / min, the hydrogen flow rate was 15 NLPM / min, the powder feeding rate was 30 g / min, the spraying distance was 15 mm, the gun travel speed was 600 mm / s, and the gun travel interval was 1 mm.

[0082] RYSZ powder (particle size of 40-140 μm) was sprayed on the YSZ layer using an atmospheric plasma spraying device to obtain a RYSZ layer with a thickness of 50 μm. The spraying current was 310A, the voltage was 42V, the power was 13.02kW, the argon flow rate was 1.8NLPM / min, the hydrogen flow rate was 14NLPM / min, the powder feeding rate was 30g / min, the spraying distance was 15mm, the gun speed was 600mm / s, and the gun interval was 1mm.

[0083] After spraying the required samples, a thermodynamic performance test was carried out, wherein the thermal shock performance was 10-15% longer than the life of Example 1, achieving the desired expected effect.

[0084] Figure 4 This is the bonding layer interface texture layer of Example 2.

[0085] Example 3

[0086] GH3230 nickel-based high-temperature alloy was selected as the substrate, and circular sheet specimens were prepared through wire cutting and polishing processing technology.

[0087] The surface of the disc was sandblasted with 36 mesh white corundum to enhance its surface roughness and adhesion, and was fully ultrasonically cleaned with alcohol and dried to obtain a GH3230 matrix.

[0088] Using atmospheric plasma spraying equipment, NiCoCrAlY (powder particle size of corresponding components is 40-140 μm; mass contents of Ni, Co, Cr, Al, Y and impurities are 38.2%, 26%, 20%, 14%, 0.8% and 1% respectively) is sprayed on GH3230 substrate to obtain a NiCoCrAlY bonding layer with a thickness of 100 μm; wherein the spraying current is 360A, the voltage is 45V, the power is 16.2kW, the argon flow rate is 2NLPM / min, the hydrogen flow rate is 18NLPM / min, the powder feeding rate is 30g / min, the spraying distance is 15mm, the gun travel speed is 600mm / s, and the gun travel interval is 1mm;

[0089] YSZ powder (particle size of 40-140 μm, Y2O3 content of 7% by mass and balance of ZrO2) was sprayed on the NiCoCrAlY bonding layer by atmospheric plasma spraying equipment to obtain a YSZ plane layer with a thickness of 100 μm. The spraying current was 330A, the voltage was 45V, the power was 14.9kW, the argon flow rate was 2NLPM / min, the hydrogen flow rate was 15NLPM / min, the powder feeding rate was 30g / min, the spraying distance was 15mm, the gun travel speed was 600mm / s, and the gun travel interval was 1mm.

[0090] After setting the baffle, continue to spray YSZ powder (particle size of 40-140μm, Y2O3 mass content of 7% in YSZ powder, balance ZrO2) to obtain cylindrical interface texture (diameter of 1.5mm, spacing of adjacent cylindrical interface textures of 1mm, height of 200μm). The power of the plasma spray gun is 37.6kW, the current is 550A, the voltage is 50V, the argon flow rate is 35.7NLPM / min, the hydrogen flow rate is 11NLPM / min, the powder feeding rate is 45g / min, the spraying speed is 800mm / s, the spraying distance between the nozzle and the GH3230 substrate is 10cm, and the gun travel interval is 1mm.

[0091] RYSZ powder (particle size of 40-140 μm) was sprayed on the YSZ layer using an atmospheric plasma spraying device to obtain a RYSZ layer with a thickness of 50 μm. The spraying current was 290 A, the voltage was 42 V, the power was 12.2 kW, the argon flow rate was 1.8 NLPM / min, the hydrogen flow rate was 14 NLPM / min, the powder feeding rate was 30 g / min, the spraying distance was 15 mm, the gun speed was 600 mm / s, and the gun interval was 1 mm.

[0092] Comparative Example 1

[0093] The only difference from Example 1 is that the YSZ interface texture layer and the RYSZ layer are not deposited.

[0094] The thermal barrier coating of Example 1 (with a cylindrical interface texture) and the thermal barrier coating of Comparative Example 1 were subjected to thermal cycle tests at 1100° C. for 50 times respectively.

[0095] The results of the thermal cycle test show that the thermal barrier coating sample with interface texture and RYSZ layer has a small peeling area, and only partial peeling occurs at the edge. However, the ordinary thermal barrier coating sample without interface texture and RYSZ layer has a large area of ​​peeling after the thermal cycle, which is defined as failure. Therefore, the performance of the thermal barrier coating sample with interface texture and RYSZ layer is better than that of the ordinary thermal barrier coating sample without interface texture and RYSZ layer.

[0096] After the YSZ layer in the thermal barrier coating of Example 1 was subjected to a thermal cycle test at 1100°C for 50 cycles, SEM analysis was performed. The results are as follows: Figure 5 As shown, the generated thermally grown oxide layer was subjected to SEM analysis, and the results are shown in Figure 6 shown.

[0097] After the YSZ layer in the thermal barrier coating (interface texture is cylindrical) of Example 1 was subjected to 50 cycles of thermal cycling at 1100°C, SEM analysis was performed. The results are as follows: Figure 7 As shown, the generated thermally grown oxide layer was subjected to SEM analysis, and the results are shown in Figure 8 shown.

[0098] Depend on Figures 5 to 8 It can be seen that after 50 thermal cycles, the interface between the bonding layer and the YSZ layer was partially oxidized into thermally grown oxide. The oxidation of the coating under the same number of thermal cycles was statistically analyzed. The results showed that the thickness of the thermally grown oxide of the sample without interface texture was 2.3 microns, and the thickness of the thermally grown oxide of the thermal barrier coating sample with interface texture was 1.7 microns. The thermally grown oxide peeling area of ​​the comparative coating was higher than that of the double-layer coating with texture designed by the present invention, and the performance of the double ceramic coating designed by the present invention was better than that of the comparative coating.

[0099] Comparative Example 2

[0100] The only difference from Example 2 is that the bonding layer, interface texture layer and RYSZ layer are not deposited.

[0101] Comparative Example 3

[0102] The only difference from Example 2 is that the diameter of the cylindrical interface texture in the bonding layer interface texture layer is 1.5 mm, the spacing between adjacent cylindrical interface textures is 1.5 mm, the height is 200 μm, and the YSZ layer is not sprayed.

[0103] Fig. 9 This is the bonding layer interface texture layer of Comparative Example 3.

[0104] The thermal barrier coatings of Example 2, Comparative Example 2 and Comparative Example 3 were subjected to 50 thermal cycle tests at 1100°C. The results are as follows: Fig.10 shown.

[0105] Depend on Fig.10 It can be seen that after a long period of thermal cycling, the coating without interface texture and RYSZ layer peeled off as a whole, while the sample with interface texture only peeled off partially. That is, the peeling area of ​​the sample with interface texture and RYSZ layer is larger than that of the sample without interface texture and RYSZ layer, indicating that under the same thermal cycling conditions, the sample with interface texture and RYSZ layer of the present invention has better performance.

[0106] Fig.11 This is the interface morphology of the thermal barrier coating with interface texture in comparative example 2. It can be observed that there are some protrusions between the interface of the bonding layer and the YSZ layer.

[0107] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A thermal barrier coating, characterized in that: It includes a NiCoCrAlY bonding layer, a YSZ layer and a RYSZ layer stacked in sequence; The composition of the RYSZ layer includes Gd2O3, Yb2O3 and ZrO2; The mass of Gd2O3 and the mass of Yb2O3 are independently 6 to 25% of the mass of ZrO2.

2. The thermal barrier coating according to claim 1, characterized in that: The thickness of the RYSZ layer is 50-150 μm.

3. The thermal barrier coating according to claim 1, characterized in that: The thickness of the YSZ layer is 100-350 μm; the mass content of Y2O3 in the YSZ layer is 7-8%.

4. The thermal barrier coating according to claim 1, characterized in that: The thickness of the NiCoCrAlY bonding layer is 40-800 μm.

5. The thermal barrier coating according to claim 1, characterized in that: The NiCoCrAlY bonding layer includes a NiCoCrAlY bonding layer plane layer and an interface texture on the surface of the NiCoCrAlY bonding layer plane layer; the interface texture is in contact with the YSZ layer; The shape of the interface texture includes one or more of a cylindrical shape, a stripe shape and a square shape.

6. The thermal barrier coating according to claim 1, characterized in that: The YSZ layer includes a YSZ plane layer and an interface texture on the surface of the YSZ plane layer; the interface texture is in contact with the RYSZ layer; The shape of the interface texture includes one or more of a cylindrical shape, a stripe shape and a square shape.

7. The method for preparing a thermal barrier coating according to any one of claims 1 to 6, characterized in that: The following steps are involved: Performing a first spraying of NiCoCrAlY powder on the metal surface to form a NiCoCrAlY bonding layer; Performing a second spraying of YSZ powder on the surface of the NiCoCrAlY bonding layer to form a YSZ layer; The RYSZ powder is sprayed on the surface of the YSZ layer for the third time to form a RYSZ layer, thereby obtaining the thermal barrier coating.

8. The preparation method according to claim 7, characterized in that: In terms of mass fraction, the NiCoCrAlY powder comprises 18-28% Co, 13-21% Cr, 10-15% Al, 0.1-0.8% Y, impurities ≤5% and the balance Ni.

9. The preparation method according to claim 7, characterized in that: When the NiCoCrAlY bonding layer includes a NiCoCrAlY bonding layer plane layer and an interface texture on the surface of the NiCoCrAlY bonding layer plane layer, the first spraying includes: first spraying to form the NiCoCrAlY bonding layer plane layer, placing a mask corresponding to the shape of the interface texture, and then performing a first spraying to form the interface texture.

10. The preparation method according to claim 7, characterized in that: When the YSZ layer includes a YSZ plane layer and an interface texture on the surface of the YSZ plane layer, the second spraying includes: after the second 'spraying forms the YSZ plane layer, placing a mask corresponding to the shape of the interface texture and then performing the second 'spraying to form the interface texture.

Citation Information

Patent Citations

  • Devices and methods for non-invasive capacitive electrical stimulation and their use for vagus nerve stimulation on the neck of a patient

    CN103517732A

  • Method for growing diamond texture coating of cutter by using shape-limiting method

    CN107523799A

  • Thermal barrier coating with structure gradient and preparation method thereof

    CN108342678A

  • Structural design and preparation method of high-strain-tolerance anti-sintering thermal barrier coating

    CN114574798A

  • Metal bonding layer and preparation method and application thereof

    CN116160019A